The Impact of Digital Media Technology on College Students’ Learning Styles - Liu, Jinhong (Education Insights, 2026)
The present research article is about the effect of digital media technology on the way how college students learn, that is, technological changes of the old education manner. A mixed-methods of data analysis and data result is used to study the changes of the way that students have learned, study, how much they are engaged and how many of them have become better. It is shown that with digital media, the learning and studying is more interactive and personal, but there are some problems e.g. cognitive overload, lower attentions. This research is helpful to understand the changes of education in the time of new technology and give the recommendations for the teachers and the politics.